Emodin Inhibits Inflammation, Carcinogenesis, and Cancer Progression in the AOM/DSS Model of Colitis-Associated Intestinal Tumorigenesis - Zhang, Yunsha; Pu, Weiling; Bousquenaud, Mélanie; Cattin, Sarah; Zaric, Jelena; Sun, Li-kang; Rüegg, Curzio (Frontiers in Oncology, 2021)
Colorectal cancer (CRC) is one of the most common cancer worldwide. Chronic inflammation contributes to CRC development and progression. Emodin, is a natural anthraquinone derivative with anti-oxidant, anti-inflammatory and anti-tumor activities. We used the AOM/DSS model of colitis-associated intestinal tumorigenesis to characterize the effect of Emodin on inflammation and tumorigenesis at weeks 3, 5 and 14 after initiation with AOM. At all three time points, Emodin (50 mg/kg) reduced inflammatory cell (i.e. CD11b+ and F4/80+) recruitment, cytokine (i.e. TNFα, IL1/, IL6, CCL2, CXCL5) and pro-inflammatory enzymes (i.e. COX-2, NOS2) expression in the tumor microenvironment, while promoting recruitment of CD3+ T lymphocytes at 14 weeks. Emodin decreased the incidence of premalignant lesions (adenoma) at week 3, the incidence of dysplastic lesions and carcinomas at week 5, and the incidence, size and the invasiveness of carcinomas at week 14. Emodin also reduced the acute clinical intestinal symptoms (i.e. bleeding and diarrhea) during DSS treatment. In vitro, Emodin inhibited the expression of pro-inflammatory mediators by LPS-stimulated RAW 264.7 macrophages, and reduced viability, adhesion, migration and fibroblasts-induced invasion of SW620 and HCT116 colon cancer cells. In conclusion, this work demonstrates that Emodin suppresses carcinogenesis-associated intestinal inflammation and prevents AOM/DSS-induced intestinal tumorigenesis and progression. These results instigate further studies on Emodin as a natural agent for the prevention or treatment of colorectal cancer.